A review of nuclear data for the k₀-based neutron activation analysis - Ho , Manh Dung; Phonesavanh, Lathdavong (Nuclear Science and Technology, 2019)
Nuclear data for the k0-based neutron activation analysis (k0-NAA) including: k0-factors – combination of nuclear constants (atomic mass, isotopic abundance, gamma-ray yield and thermal neutron capture cross section); Q0 – the ratio of the resonance integral to thermal neutron capture cross section; and Er – effective resonance energy, along with the related nuclear data are presented and evaluated in the presentation. Accuracy and capability of k0-NAA depends considerably on the reliability of the above mentioned nuclear data. In general, the evaluation of nuclear data is essential and necessary in the field of nuclear science and technology, and this work is conducted by the nuclear data centers on the world as well as the research institutions where the nuclear data are used for R&D. Therefore, the evaluation of the nuclear data used in k0-NAA should also be performed so that some of data may no longer be appropriate should be redetermined. The evaluation of nuclear data in k0-NAA would contribute to the improvement of accuracy and reliability of the method, moreover, it would also contribute to the establishment a nuclear database in Vietnam in the future.